Modernisasi Konsep Kafa'ah dalam Pernikahan: Temuan Studi Kasus di Keluarga Kiai Desa Prajjan - Amin Jakfar (At-Tafakur: Jurnal Ilmu Syari'ah dan Hukum, 2024)
This study examines the dynamics of the application of the concept of kafa'ah (equality) in marriage among Kiai's children in Prajjan Village, Camplong, Sampang, with the aim of understanding changes in perceptions of marriage criteria in social and religious contexts. Using a qualitative approach and case study method, this study found that although equality in lineage is still dominant, there is a shift in thinking among the younger generation who have begun to consider aspects of taqwa, morals, and religious commitment as important criteria in choosing a spouse. The findings suggest that education level and social experience influence flexibility in the application of the concept of kafa'ah, with Kiai's children who have formal education being more open to more inclusive interpretations. The research also proposes modifications to the concept of kafa'ah to include broader spiritual and moral dimensions, in accordance with Islamic principles of justice. The implications of these findings are important for policy makers, educators and religious leaders in developing a balanced approach to social and religious norms, as well as opening up opportunities for further research into the evolution of traditional norms in contemporary Muslim communities.